2022
DOI: 10.3389/fpos.2022.907681
|View full text |Cite
|
Sign up to set email alerts
|

The fascist authoritarian model of illiberal democracy

Abstract: Based on our observations and scholarship about how democratic norms are currently being undermined, we propose a model of fascist authoritarianism that includes authoritarianism, the production and exaggeration of threats, conspiracy-oriented propaganda adoption, and distrust of reality-based professions. We refer to this as the Fascist Authoritarian Model of Illiberal Democracy (FAMID) and argue that all components are essential for understanding contemporary antidemocratic movements. We demonstrate that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Consistent with what has been found in different reports Latinobarómetro, 2018;Schmitz & Espinosa, 2015), people's distrust of institutions is accompanied by a lack of interest in political and public affairs, which increases the scope for political operators to concentrate political power and corruption (Barrenechea & Vergara, 2023;Dunwoody et al, 2022;Ilizarbe, 2023). This gives way to an evaluation of the concept of illiberal democracy, which becomes a form of political clientelism of state capitalism Kramer, 2022).…”
Section: Introductionsupporting
confidence: 66%
“…Consistent with what has been found in different reports Latinobarómetro, 2018;Schmitz & Espinosa, 2015), people's distrust of institutions is accompanied by a lack of interest in political and public affairs, which increases the scope for political operators to concentrate political power and corruption (Barrenechea & Vergara, 2023;Dunwoody et al, 2022;Ilizarbe, 2023). This gives way to an evaluation of the concept of illiberal democracy, which becomes a form of political clientelism of state capitalism Kramer, 2022).…”
Section: Introductionsupporting
confidence: 66%
“…Misinformation is seen as a significant contributor to illiberal and extremist attitudes (Vosoughi et al, 2018). Political leaders with illiberal or populist tendencies rely, as a strategy, on flooding the information ecosystem with a wave of misinformation that ultimately makes it extremely difficult for regular audiences to discern fact from fake (Dunwoody et al, 2022). In the particular context studied in this paper, specific pro-Russian narratives present in social media (Geissler et al, 2023; Hanley et al, 2023) might a lead to more open manifestation of illiberal attitudes in the target population.…”
Section: Factors That Impact Illiberal Attitudesmentioning
confidence: 99%
“…Classical research has suggested that threats against social conformity "activate" the antidemocratic potential in authoritarians, yielding intolerance and prejudice against those who deviate from social conventions (Feldman, 2003;Feldman & Stenner, 1997;Stenner, 2005). Less is known about the effects of threats against progressive values, but some studies have suggested that perceived threat from political opponents is a major predictor of willingness to support violence against them and restrictions of their democratic rights among both liberals and conservatives (Crawford & Pilanski, 2014;Dunwoody et al, 2022). Nevertheless, recent studies suggest that there are differences at least in perceptions of threat, consistent with the proposed account (Brandt et al, 2021;Kahn et al, 2022): right-wing conservative ideology tends to be associated with concern about terrorism, war, and immigration (i.e., threats to the normative order), while left-wing ideology tends to be associated with concern about poverty, climate change, inequality, and racism (i.e., threats to progressive values).…”
Section: Antidemocratic Predispositions On the Left And The Rightmentioning
confidence: 99%
“…Similarly, a belief that society is deeply corrupt or unjust that is rooted in perceived deprivation or grievance is often described as an early antecedent of political radicalism and violence (Armaly & Enders, 2022;Becker & Tausch, 2015;Moghaddam, 2005), and this belief is consistent with both left-and right-wing identity politics and populism (e.g., construing society as racist or the elite as corrupt). Furthermore, a receptivity to fake news, conspiracy theories, and other kinds of misinformation may make people more susceptible to antidemocratic ideas, particularly insofar as it leads to a "post-truth" reliance on subjective opinions, intuitions, and rhetoric instead of scientific facts, legitimate expertise, and rigorous journalism (Lewandowsky et al, 2017)-or a "truth delegitimization" (Dunwoody et al, 2022). In addition, perceptions concerning the epistemic and moral superiority or significance (e.g., chosenness) of the self or the ingroup might help to explain why people come to feel entitled to impose their beliefs on others through coercion or violence (Altemeyer, 1988;Webber et al, 2020).…”
Section: Concluding Remarks: Toward a Modern Synthesismentioning
confidence: 99%
See 1 more Smart Citation